The treatment of gingival recession with coronally advanced flap with platelet-rich fibrin - Asti Rosmala Dewi; Agus Susanto; Yanti Rusyanti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: Of the various techniques developed for the treatment of gum recession, the current innovation in the use of platelet rich plasma (PRF) has been applied to the treatment of root-end closure procedures. Purpose: This study analyzed the effect of the coronally advanced flap (CAF) in combination with platelet-rich fibrin (PRF) during treatment of gingival recession. Methods: This research constituted an experimental study incorporating a split-mouth design which was conducted on eight participants (with 16 recession defects) who were divided into two groups consisting of the CAF group with PRF and another CAF group without PRF. Clinical parameters consisting of gingival recession (GR), keratinized gingival width (KGW), recession width (RW) and clinical attachment level (CAL) were measured both before and 21 days after surgery). Results: The average differences between clinical parameters in the test group were as follows: GR (2.25 ± 0.27), KGW (1.81 ± 0.75), RW (3.44 ± 1.35), and CAL (2.56 ± 0.50); while in the control group they were as follows: GR (2.00 ± 0.71), KGW (1.94 ± 0.78), RW (3.50 ± 1.91) and CAL (2.00 ± 0.76). There were significant differences in the GR and CAL between the test and control groups (p ≤ 0.05). Conclusion: A combination of the CAF procedure and PRF was proven to be more effective in covering the GR and increasing the CAL.